A comprehensive systematic review and meta-analysis on the extraction of pesticide by various solid phase-based separation methods: a case study of malathion. Issue 5 (9th April 2023) - Yeganeh, Mojtaba; Azari, Ali; Sobhi, Hamid Reza; Farzadkia, Mahdi; Esrafili, Ali; Gholami, Mitra
ABSTRACT: Malathion is one of the most well-known pesticides which is widely used for controlling insects and pests. Slow degradation and extensive and/or inappropriate use of malathion have resulted in the contamination of the environment inflicting hazardous damages to the ecosystems and human health. This systematic study along with meta-analysis is aimed at reviewing a vast number of reports on the application of the above-mentioned methods used for the extraction and detection of malathion in a wide variety of samples. Initially, the relevant articles over the last decade (2011-2020) were selected for the meta-analysis and subsequently systematically reviewed. The major key points of each article were extracted by a predefined data template. In addition, the statistical analyses were performed by the R software. Following a thorough screening, 812 articles were found to be suitable. Of which, 68 were finally selected which met the required quantitative criteria for the meta-analysis. Meta-analysis was conducted by the random-effects model with a high heterogeneity (I2 = 99.99%). The pooled results on the selected articles revealed that the solid phase-based methods in combination with gas chromatography-mass spectroscopy (GC-MS) have gained lots of interest among the researchers. Within the mentioned articles, the respective recoveries, LODs and LOQs were reported to fall in the range of 95.43-139%, 0.000026-100 µg/l, 0.000078-300 µg/l and 97.20-136%, 0.00001-1.3 µg/g, 0.00005-4.2 µg/g for the aqueous and solid matrices. The results also revealed that the maximum recovery was affiliated to the SPE method (139%) for the aqueous matrices, while the corresponding value for the solid matrices was 134%. According to the pooled data, the mean recoveries varied in the ranges of 92.11-102.50 % and 92.21-102.91% in the aqueous and solid matrices, respectively. The maximum recovery of malathion was assigned to the extraction by SPE (101.46%, 95% CI= 94.66-108.27).